A pathogenesis-related protein 1 of Cucurbita moschata responds to powdery mildew infection - Guo, Wei-Li; Yang, He-Lian; Zhao, Jin-Peng; Bian, Shi-Jie; Guo, Yan-Yan; Chen, Xue-Jin; Li, Xin-Zheng (Frontiers in Genetics, 2023)
Pumpkin (Cucurbita moschata Duch.) productivity is severely hindered by powdery mildew (PM) worldwide. The causative agent of pumpkin PM is Podosphaera xanthii, a biotrophic fungus. Pathogenesis-related protein 1 (PR1) homolog was previously identified from transcriptomic analysis of a PM-resistant pumpkin. Here, we investigated the effects of CmPR1 gene from pumpkin for resistance to PM. Subcellular localization assay revealed that CmPR1 is a cytoplasmic protein in plants. The expression of CmPR1 gene was strongly induced by P. xanthii inoculation at 48 h and exogenous ethylene (ET), jasmonic acid (JA) and NaCl treatments, but repressed by H 2 O 2 and salicylic acid (SA) treatments. Visual disease symptoms, histological observations of fungal growth and host cell death, and accumulation of H 2 O 2 in transgenic tobacco plants indicated that CmPR1 overexpression significantly enhanced the resistance to Golovinomyces cichoracearum compared to wild type plants during PM pathogens infection, possibly due to inducing cell death and H 2 O 2 accumulation near infected sites. The expression of PR1a was significantly induced in transgenic tobacco plants in response to G. cichoracearum, suggesting that CmPR1 overexpression positively modulates the resistance to PM via the SA signaling pathway. These findings indicate that CmPR1 is a defense response gene in C. moschata and can be exploited to develop disease-resistant crop varieties.